2022
DOI: 10.3390/ijerph19042278
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of COVID-19 on Healthcare Quality in Tertiary Medical Centers—A Retrospective Study on Data from Taiwan Clinical Performance Indicators System

Abstract: To date, COVID-19 is by far the most impactful contagious disease of the 21st century and it has had a devastating effect on public health in countries around the globe. Elective medical services have declined markedly since the outbreak of the COVID-19 pandemic. Few studies have compared changes in healthcare quality before and during the outbreak of COVID-19 in Eastern Asian countries. We aimed to explore the impacts of COVID-19 on healthcare quality among medical centers in Taiwan. This was a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
5
0
2
Order By: Relevance
“…Previous studies have investigated the impact of the COVID-19 pandemic in the acute care setting on speci c countries (23,203,199,201), phases of the pathway (136, 201), or diseases (197,202,204). This scoping review provides a comprehensive overview of the changes reported on the quality of acute care during the rst year and a half of the COVID-19 pandemic, covering OECD countries, multiple diseases, and following a care pathway approach.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the impact of the COVID-19 pandemic in the acute care setting on speci c countries (23,203,199,201), phases of the pathway (136, 201), or diseases (197,202,204). This scoping review provides a comprehensive overview of the changes reported on the quality of acute care during the rst year and a half of the COVID-19 pandemic, covering OECD countries, multiple diseases, and following a care pathway approach.…”
Section: Discussionmentioning
confidence: 99%
“…Medical centres in Taiwan also provide the highest level of medical care as accredited by the Joint Commission of Taiwan (JCT), under the supervision of the Ministry of Health and Welfare of Taiwan (MOHW). 27 However, along with clinical services, research and education, medical centres are also responsible for conveying the proper health information to the public, including what they post on platforms such as Facebook or YouTube.…”
Section: Objectivesmentioning
confidence: 99%
“…Academic medical centres in Taiwan serve as healthcare institutions having multiple functions, including diagnosis and treatments of disease, advanced research regarding pathogens and underlying mechanisms, and medical education for the younger generation of healthcare professionals. Medical centres in Taiwan also provide the highest level of medical care as accredited by the Joint Commission of Taiwan (JCT), under the supervision of the Ministry of Health and Welfare of Taiwan (MOHW) 27. However, along with clinical services, research and education, medical centres are also responsible for conveying the proper health information to the public, including what they post on platforms such as Facebook or YouTube.…”
Section: Objectivesmentioning
confidence: 99%
“…En esa línea, cabe resaltar que los proveedores de servicio o prestación de atención, en este caso, los establecimientos sanitarios, permiten identificar que los usuarios tienen una percepción acerca de la gestión realizada en los mencionados, teniendo como base ISN 2707-2207/ISSN 2707-2215 (en línea),septiembre-octubre,2022,Volumen 6,Número 5 p 3221 los aspectos tangibles, que en su mayoría se trata de la infraestructura, evidenciando elementos seguros para la intervención de los pacientes, incidiendo en la seguridad y fiabilidad en la que se encuentran los usuarios (Mrabet et al, 2022). En ese orden de ideas, Liu et al (2022) quienes refirieron que los servicios médicos fueron calificados como buenos, a pesar las circunstancias obtenidas por la pandemia por las que se atraviesa, se ha visto que constantemente se dio la mejora de herramientas tecnológicas y en la gestión favorable de los establecimientos de salud.…”
Section: Categoría Calidad De Atenciónunclassified